Ecological discourse analysis of Russian educational texts based on the transitivity system - Luan Luan; Dong Zhang (Cogent Arts & Humanities)
Ecological discourse within educational contexts serves as an externalized manifestation for scholars and educators in ecolinguistics to embrace ecological responsibilities and convey positive ecological philosophies. While ecological discourse analysis predominantly employs English as its analytical language, exploration of discourse analysis models based on other languages remains scarce. Therefore, this study, grounded in Halliday’s Systemic Functional Linguistics and the Transitivity Theory, aims to refine the roles of participants, process semantics, and environmental components. Through qualitative and quantitative research, it investigates college-level Russian educational discourses under the guidance of ecological philosophy to unveil their ecological orientation.